Industrial Piping System: Design and Corrosion Protection - David Coverdale Rangel Velasco; Victor Paes Dias Gonçalves; Michel Picanço Oliveira; Noan Tonini Simonassi; Felipe Perissé Duarte Lopes; Carlos Maurício Fontes Vieira (Surfaces)
Piping system failures in process industries pose significant financial, environmental, and social risks, with inadequate design and corrosion being major contributors. This review synthesizes the academic and normative literature on pipeline design and anticorrosive protection strategies, providing a comprehensive examination of pipeline layout determination, material selection, and methods for mitigating corrosion. A particular focus is placed on organic coating as a pivotal strategy for corrosion reduction, with in-depth insights into their selection and evaluation criteria. By highlighting best practices and advancements in design and protection strategies, this review aims to enhance the overall integrity and safety of piping systems. The findings are intended to support industry professionals in implementing more effective measures to prevent pipeline failures and improve system reliability, while also presenting recent advances and current demands.